Medical Advances in the Treatment of Postpartum Hemorrhage. Issue 3 (September 2015) - Ducloy-Bouthors, A.S.; Susen, S.; Wong, C.A.; Butwick, A.; Vallet, B.; Lockhart, E.
Abstract : ( Anesth Analg . 2014;119(5):1140–1147)